Valência do nome deverbal e nominalidade prototípica - Camacho, Roberto Gomes [UNESP] (Pontifícia Universidade Católica de São Paulo (PUC-SP), 2007)
O objetivo deste trabalho é mostrar que os nomes deverbais preservam a estrutura argumental do verbo input correspondente e que a especificação ou não dos argumentos no interior do termo nominal depende de um conjunto de fatores pragmáticos, especialmente relacionados a informação de curto termo compartilhada pelos participantes da interação. Como implicação teórica, a análise preserva a idéia de que há um processo gradual de descategorização verbal, que se reflete nos diferentes tipos de marcação gramatical. Conforme o predicado verbal ganha estatuto nominal, as marcações tipicamente oracionais dão lugar a outros mecanismos, como marcação argumental por preposição, modificação por adjetivo, uso de pronomes possessivos, que acompanham apropriadamente um núcleo nominal.

This paper aims to show that deverbal nouns preserve the argument structure of the corresponding input verb and that the overt or non-overt expression of their arguments within the term depends on a set of semantic and pragmatic factors, mainly related to the shared short-term information by the speech act participants. As a theoretical implication, this analysis preserves the idea that there is a gradual process of verbal decategorization, which is reflected in the different kinds of grammatical relation markings. As the verbal predicate gradually gains nominal status, the clausal markings (agreement, word order and the like) give way to prepositional marking or some other device, like adjectival modification or the use of possessive pronouns which are perfectly appropriate to follow a nominal head.
Valency of deverbal nouns and prototypical nominality
Keywords: Nominalization; deverbal noun; verbal decategorization; Parts of speech; Nominalização; nome deverbal; descategorização verbal; classes de palavra